The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/ijms21228762
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Vesicles in Epithelial Ovarian Cancer: A Systematic Review

Abstract: Extracellular vesicles (EVs) are a heterogeneous group of cell-derived submicron vesicles released under physiological or pathological conditions. EVs mediate the cellular crosstalk, thus contributing to defining the tumor microenvironment, including in epithelial ovarian cancer (EOC). The available literature investigating the role of EVs in EOC has been reviewed following PRISMA guidelines, focusing on the role of EVs in early disease diagnosis, metastatic spread, and the development of chemoresistance in EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 98 publications
0
50
0
Order By: Relevance
“…The four most common subtypes of EOCs are serous, endometrioid, clear cell, and mucous carcinoma ( 2 ). EOC is diagnosed with advanced disease in ~70% of the patients ( 4 ). Although debulking surgery combined with neoadjuvant or adjuvant platinum- or purple gold-based chemotherapy has become the standard treatment approach for patients with advanced EOC, survival rates for advanced ovarian cancer are still low, patients who are classified as stage III and IV under the Federation International of Gynecology and Obstetrics (FIGO) have the 5-year survival rates of only 42 and 26%, respectively ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The four most common subtypes of EOCs are serous, endometrioid, clear cell, and mucous carcinoma ( 2 ). EOC is diagnosed with advanced disease in ~70% of the patients ( 4 ). Although debulking surgery combined with neoadjuvant or adjuvant platinum- or purple gold-based chemotherapy has become the standard treatment approach for patients with advanced EOC, survival rates for advanced ovarian cancer are still low, patients who are classified as stage III and IV under the Federation International of Gynecology and Obstetrics (FIGO) have the 5-year survival rates of only 42 and 26%, respectively ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that miRNAs could be transferred between cells via EVs [ 6 , 7 , 21 ]; thus, we wondered whether PC3-derived EVs could transfer miRNA Let-7b to THP-1 cells. We exposed THP-1 monocytic cells, after TPA differentiation into M0 macrophages, to 100 μg/mL PC3-EVs for different times and observed the appearance of red fluorescent EV-like particles in the cytoplasm after 30 min incubation ( Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, prostatic fluid contains extracellular vesicle (EVs), historically known as prostasomes, which are released into the lumen of the prostatic ductal system from the epithelial cells of the gland [ 4 ]. A growing body of evidence indicates that cell-cell communication between cancer cells and other cells of the tumor microenvironment is pivotal for cancer progression [ 5 , 6 , 7 ]. Among the communication systems, prostate-derived extracellular vesicles (pEVs) have received particular attention for their involvement in the initiation, progression and metastasis of prostate cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes from ovarian cancer cells can activate Toll Like Receptor (TLR) signaling in monocytes leading to IL-6 production. Activation of STAT3 by IL-6 contributes to the immunosuppressive phenotype of the tumor microenvironment [ 64 ]. At the interface between the adaptive and innate arms of the immune system are professional antigen presenting cells (APCs) that can present antigen while providing costimulatory signals to antigen-specific T cells.…”
Section: Evs In Ovarian Cancermentioning
confidence: 99%